PENGARUH AUDIT JUDGMENT, PENGALAMAN AUDITOR, DAN ETIKA AUDITOR TERHADAP PEMBERIAN OPINI AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) DI MAKASSAR - Anwar Anwar (AkMen JURNAL ILMIAH, 2018)
This study aims to determine whether Audit Judgment, Auditor Experience, and Auditor Ethics have an effect on the giving of Audit Opinion to Public Accounting Firm (KAP) in Makassar. Data collection used primary data obtained from questionnaires using saturated sample technique. The population is all auditors in five (5) Public Accounting Firm in Makassar a total of 33 auditors, and the entire sample is used in this study. The results of the questionnaire have been tested for validity and reliability, also tested the classical assumption of normality assumption, and multicolonierity assumption. Methods of data analysis using multiple regression techniques. The results showed that the proposed hypothesis was accepted because it showed positive and significant hypothesis test results. This means that Audit Judgment, Auditor Experience, and Auditor Ethics have a positive and significant impact on Audit Audit Opinion at Public Accounting Firm (KAP) in Makassar.